Microfinance and economic empowerment: Comparative case studies of rural regions in Thailand, Vietnam, and Philippines - Phan , Khanh Duy; Nguyen , Truong Thanh Thao; Mai , Le Quynh (Journal of Finance - Marketing Research, 2025)
This study assesses the causal impact of microfinance on rural development in Thailand, Vietnam, and the Philippines using a Propensity Score Matching and Difference-in-Differences (PSM–DiD) approach. Based on data from 1,200 households, we estimate effects on income, business ownership, and educational spending. Results show significant gains: household income rose by 40.10, 28.45, and 50.33; business ownership rose by 10, 6, and 12 percentage points; and educational spending by 15%, 10%, and 20% in Thailand, Vietnam, and the Philippines, respectively. Impacts were strongest among women and youth. Comparative evidence highlights the influence of institutional design, with the Philippines’ mature microfinance system yielding the largest effects. Robustness checks confirm internal validity. We propose four targeted policy actions: interest rate subsidies, regulatory reform in Vietnam, financial literacy integration, and gender-focused lending. These findings offer practical insights for enhancing microfinance outcomes across diverse Southeast Asian contexts.